2006
DOI: 10.1142/s0192415x06004041
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of Cinnamon Oil and Cinnamaldehyde from the Chinese Medicinal HerbCinnamomum cassiaBlume

Abstract: Both Cinnamomum verum J.S. Presl. and Cinnamomum cassia Blume are collectively called Cortex Cinnamonmi for their medicinal cinnamon bark. Cinnamomum verum is more popular elsewhere in the world, whereas C. cassia is a well known traditional Chinese medicine. An analysis of hydro-distilled Chinese cinnamon oil and pure cinnamaldehyde by gas chromatography/mass spectrometry revealed that cinnamaldehyde is the major component comprising 85% in the essential oil and the purity of cinnamaldehyde in use is high (> … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
158
2
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(191 citation statements)
references
References 13 publications
14
158
2
6
Order By: Relevance
“…Ooi et al found that both oil and pure cinnamaldehyde of C. cassia were equally effective in inhibiting the growth of bacteria including Gram positive and Gram negative and fungi. They concluded that broad- spectrum antibiotic activities of C. cassia oils are due to cinnamaldehyde [23] . Siddiqua et al found that cinnamaldehyde and clove oils showed effective antibacterial activity and when combined, the activity increased [24] .…”
mentioning
confidence: 99%
“…Ooi et al found that both oil and pure cinnamaldehyde of C. cassia were equally effective in inhibiting the growth of bacteria including Gram positive and Gram negative and fungi. They concluded that broad- spectrum antibiotic activities of C. cassia oils are due to cinnamaldehyde [23] . Siddiqua et al found that cinnamaldehyde and clove oils showed effective antibacterial activity and when combined, the activity increased [24] .…”
mentioning
confidence: 99%
“…As atividades antimicrobianas dos óleos de C. cassia e T. vulgaris, avaliadas por diferentes metodologias, já são bem relatadas na literatura para uma série de microorganismos patogênicos (Ooi et al, 2006;Oussalah et al, 2007;Abdollahzadeh et. al., 2014;Dussault et al, 2014;Pekmezovic et al, 2015).…”
Section: Resultsunclassified
“…Essential oils from C. verum and C. cassia and pure cinnamaldehyde were inhibitory for bacteria (Table 5), yeasts (C. albicans, C. glabrata, C. tropicalis and C. krusei), for moulds and dermatophytes (Ooi et al, 2006). Also Matan et al (2006) found that the antifungal activity of cinnamon and clove oils volatile against spoilage fungi, yeasts and bacteria.…”
Section: Plant Extracts With Anti-bacterial Activitiesmentioning
confidence: 97%
“…Eugenol dominates in oils from clove (Syzygium aromaticum) and cinnamon (Cinnamomum zeylanicum) (Dušan et al, 2006). Cinnamaldehyde is the main component of C. verum or C. cassia (Ooi et al, 2006). Essential oils themselves make 1.5% to 4.5% of the plant (Bozin et al, 2006;Hazzit et al, 2006;Yang et al, 2007).…”
Section: Plant Extracts With Anti-bacterial Activitiesmentioning
confidence: 99%